Preoperative portal vein embolization followed by right hepatectomy to treat a complex common bile duct injury in a 5-year-old child - Juan Glinka; Rocio Bruballa; Martin de Santibañes; Rodrigo Sanchez Clariá; Victoria Ardiles; Oscar María Mazza; Juan Pekolj; Eduardo de Santibañes (BMJ Publishing Group, 2019)
Background Common bile duct injuries (CBDIs) remains a rare but serious complication in children undergoing laparoscopic cholecystectomy (LC), with an incidence of 0.44%. In severe lesions, a major liver resection may be necessary as a definitive treatment. The current principles for safe hepatectomy are mainly focused on the liver parenchyma that remains after resection. Therefore, one of the main factors related to posthepatectomy hepatic insufficiency is the quantity and quality of the future liver remnant (FLR). To achieve an optimal FLR, techniques such as portal vein embolization (PVE) are available.Case presentation We present the case of a 5-year-old child with a severe CBDI after LC, treated with preoperative PVE followed by a right hepatectomy as definitive treatment. No reports of liver resections and PVE are described in the literature concerning the pediatric population.